Pengaruh Penambahan Emulsifier terhadap Mutu Sensori Roti Tawar selama Penyimpanan - Andreas Dalton; Sugiyono Sugiyono; Elvira Syamsir (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2016)
This study was aimed to determine the effect of emulsifier addition to the quality sensory of fresh bread during storage and to determine the choosen concentration of emulsifier. The emulsifier of mono and diglycerides was added into flour along with other raw materials. The bread was processed with direct method. In this experiment, two treatments were applied, i.e. emulsifier concentration (0.1, 0.2, 0.3, 0.4, 0.5% to the weight of wheat flour) and storage at room temperature (1,2,3,4 days). Sensory tests were done each day using a scoring method with six trained panelists. Sensory parameters tested consist of external characteristics (volume, color of crust, symetry of form, character of crust) and inter-nal characteristics (crumb,color crumb, aroma, taste, texture, and chewing). The results of the research showed that the emulsifier did not affect significant external quality of pan bread. but emulsifier could improve significant the quality of sensory pan bread (texture and mastication). During storage there were decreases in the internal quality in all pan bread, but pan bread with the addition of emulsifiers had a better quality than pan bread without emulsifiers. The addition of emulsifier could not reduce staling. The choosen concentration of emulsifier was 0.1% of wheat flour.